Enhancing Learning Outcomes for Children with Autism: The Role of Specialized Educational Interventions - Saha, Priyanka (RESEARCH HUB International Multidisciplinary Research Journal, 2022)
Because of their abnormalities in cognitive processing, communication, and social interaction, children with Autism Spectrum Disorder (ASD) have great difficulties in conventional learning settings. The purpose of this paper is to investigate how specific educational interventions might improve the learning results for autistic youngsters. Grounded in accepted theoretical frameworks including Applied Behaviour Analysis (ABA), Vygotsky’s Social Constructivist Theory, Universal Design for Learning (UDL), Sensory Integration Theory, and the DIR/ Floortime Model, this study investigates evidence-based teaching approaches supporting cognitive and social development. The study emphasizes how inclusive education, assistive technology, tailored training, and peer-mediated interventions support significant learning opportunities. It also examines the difficulties of putting particular interventions—including accessibility, teacher preparation, and limited resources—into effect. According to the study, maximizing educational solutions for children with autism requires a multi-theoretical, multidisciplinary approach. Future research should focus on adding neurodiverse-inclusive policy and technology advances to generate adaptable and environmentally friendly educational settings.